Development of Dynamic Model and Analytical Analysis for the Diffusion of Different Species in Non-Newtonian Nanofluid Swirling Flow - Usman, Auwalu Hamisu; Khan, Noor Saeed; Humphries, Usa Wannasingha; Shah, Zahir; Kumam, Poom; Khan, Waris; Khan, Amir; Rano, Sadiya Ali; Ullah, Zafar (Frontiers in Physics, 2021)
The analysis is carried out to analyze the flow through double stretchable rotating disks with the theory of radiative Cross-nanofluid under the influence of variable thermal conductivity, the Hall current, Arrhenius activation energy and binary chemical reactions. The Buongiorno nanofluid model is adopted for the governing equations of the problem which are transformed into ordinary differential equations through similarity transformations and then solved using the homotopy analysis method (HAM). The impact of dimensionless parameters on all profiles and physical quantities are presented and discussed. The radial velocity of the two disks increases with their corresponding ratio stretching rate parameter and decreases with the Hall parameter and the bioconvection Rayleigh number. The heat transfer at the lower disk enhances with the variable thermal conductivity parameter while at the upper disk opposite trend is observed. Mass transfer increases with the chemical reactions and temperature difference parameters at the lower disk and decreases with Arrhenius activation energy whereas an opposite trend is observed at the upper disk. The local density number is enhanced for the larger values of Peclet and Lewis numbers. The comparison of the present work with the published literature authenticates the validation of the present work.